REPRESENTATION OF THE SEARCH FOR IDENTITY IN THE ANIMATED FILM JUMBO: A SEMIOTIC ANALYSIS BY ROLAND BARTHES - Ahmad Hamzah; Arvin Hardian (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to analyze the representation of identity search in the Indonesian animated film Jumbo through the lens of Roland Barthes' semiotics. The research focuses on interpreting visual and narrative signs that reflect the dynamics of urban youth life in Jakarta. A qualitative descriptive-interpretative method with a single case study design was employed. Data were collected through repeated observations of the film and literature reviews, then analyzed using Barthes' three-layer semiotic framework: denotation, connotation, and myth. The findings reveal that the search for identity is represented in layered meanings. At the denotative level, signs such as the protagonist's giant body, Jakarta's traffic congestion, and bullying scenes depict physical isolation and social pressure. At the connotative level, these signs symbolize emotional alienation and identity crises caused by urban pressures. At the mythological level, the film naturalizes identity crises as an inevitable consequence of metropolitan life while reproducing the ideology of conformity as a solution to social pressure. This research contributes to the development of visual semiotics studies and communication within the context of local Indonesian animation